Phylogeographic Analysis and Identification of Factors Impacting the Diffusion of Foot-and-Mouth Disease Virus in Africa - Duchatel, Florian; Bronsvoort, Barend M. de C.; Lycett, Samantha (Frontiers in Ecology and Evolution, 2019)
Foot and mouth disease (FMD) is endemic in sub-Saharan Africa. Due to the complexity of the disease epidemiology and the lack of data available there is a need to use modelling approaches to fill the gaps in our understanding of the virus circulation on this continent. Using a phylogeographic approach we reconstructed the circulation of FMD virus serotypes A, O, SAT1 and SAT2 in Africa and evaluated the influence of potential environmental and anthropological predictors of virus diffusion. Our results show that the serotypes O and A were introduced to Africa over the last century while the SAT1 and SAT2 serotype have been circulating for at least 400 years in wildlife. Our results also suggest that outside Southern-Africa wildlife does not play a role in the maintenance and circulation of the disease within the domestic animals. Further, the circulation of serotype O in eastern Africa appears to be facilitated by both indirect transmission through persistence in the environment and anthropological activities such as cattle movements. Evidence for the different epidemiologies of serotypes has been lacking but is essential in developing a modern approach to control of FMD viruses in Africa.